Business services in Germany: bridges for innovation - Dirk Czarnitzki; Alfred Spielkamp (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
During the last 20 years, R&D and innovation activities in the service sector have clearly increased. Especially business services are believed to be one of the main drivers of technical changes and economic progress. Looking at the labour indices calculated over the period from 1982 to 1996 one notices a remarkable increase of over 70 percent for the business services. About 8 percent of total employment in West Germany is in business services. In particular, by taking advantage of information and communication technologies, knowledge-intensive business service firms increasingly play the role of "converters" of technological information within the economy. They are providers, purchasers or partners in the context of innovation. A sound innovation capacity, especially knowledge, creativity, market and management skills let them become bridges for innovation.
Keywords: C20; O30; L80; L11; D21; 330; Business Services; R&D; Innovation; Technical Change; ICT; Knowledge Flows; Unternehmensdienstleistung; Innovation; Forschung; Wissenstransfer; Deutschland